ATLAS simulation of LWIR photodetector based on mercury cadmium telluride - Saxena P.K.; Chakrabarti P. (My University, 2025)
In the present paper the performance of p+-n0-n + homojunction Hg1-xCdxTe (λ c=10.6μm) photodetector has been analyzed theoretically at 77K. Electrical characterization of the homojunction photodetector has been carried out using ATLAS software of SILVACO® and the results are compared and contrasted with the results of our theoretical model The dependence of the p+-n0 junction position within homostructure on bandgap energy profiles and the influence of doping concentration on photodetector parameters have been studied. The dark current-voltage characteristics and dynamic resistance versus voltage are simulated and analyzed theoretically. Results of our study reveal that suitable biasing conditions the photodetector exhibits a dark current, ID ≈ 10-7 A, and a zero bias resistance, R0 = 106Ω. ©2007 IEEE.